Origin of resistance against desiccation and cryoinjuries in soil crust microalgae of High Arctic - Frank, Elisa (Jihočeská univerzita, 2023)
Microalgae of polar soil crusts are of significant ecological importance by regulating numerous vital processes in the extreme Arctic climate. To protect themselves from these harsh conditions they developed various adaption mechanisms. Hardening and nutrient starvation during the late summer months are expected to positively impact the resistance of microalgae against cryoinjuries and desiccation. The first aim of this study was to assess the vitality of microalgae in biological soil crusts within the High Arctic (Central Svalbard) during the summer using multiple approaches. The second objective was to perform an evaluation of the biodiversity and a viability growth test of microalgae within the cryptogamic crusts, providing an overview of the species composition and vitality.
Origin of resistance against desiccation and cryoinjuries in soil crust microalgae of High Arctic
Keywords: Microalgae; High Arctic; Biological soil crusts; Hardening; Starvation; Microalgae; High Arctic; Biological soil crusts; Hardening; Starvation